Source Domains of Smell Related Metaphorical Collocations: Study Based on Corpus of Contemporary American English - Selmistraitis, Linas; Boikova, Renata (Respectus Philologicus, 2020)
The paper discusses source domains of smell related metaphorical collocations. The research is limited to metaphorical collocations with pleasant smell denoting words scent, fragrance, aroma, and perfume in the Corpus of Contemporary American English (COCA). The scope of the research is 2187 concordance lines (CL) containing metaphorical collocations with the words scent, fragrance, aroma, and perfume from 3580 CL containing any word phrase with the target words. The research is based on identification and description of the source domains of the collected metaphorical collocations with pleasant smell words, relating the source domains to underlying conceptual metaphors and determining the frequency distribution of the identified source domains. The following source domains were identified in the research: object, substance, physical force, and food. The analysis showed the frequency of source domains across all four groups forming smell related conceptual metaphors: object with 1833 instances of metaphorical collocations (84%), substance with 202 instances (9%), physical force with 130 instances (6%), and food with 22 instances (1%). The present study contributes to the development of cognitive semantics and its findings demonstrate which meanings are prevalent in human mentality when pleasant smell related metaphorical collocations are used.
Keywords: cognitive linguistics; corpus linguistics; conceptual metaphor; source domain; COCA